(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The purpose of the article is to theoretically substantiate monitoring the knowledge of students with the help of tests is gaining a stronger position in the system of educational institutions in our country every year. At the same time, directly for the students themselves, this is a fairly new and, for many, unusual form of knowledge control. At the stage of transition to mass and widespread testing, when it has not yet become common and familiar to most schools, it is very important to create a positive attitude among pupils towards this method of monitoring knowledge. The reasons and circumstances of such influence can be very different. It is therefore important for test organizers and teachers to know and anticipate these types of influences and be able to compensate for them with the help of special events and actions.